1999
DOI: 10.1128/jb.181.8.2648-2651.1999
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis waaAEncodes a Monofunctional 2-Keto-3-Deoxy-d-manno-Octulosonic Acid Transferase That Can Complement anEscherichia coli waaAMutation

Abstract: Bordetella pertussis lipopolysaccharide (LPS) contains a single 2-keto-3-deoxy-d-manno-octulosonic acid (Kdo) residue, whereas LPS from Escherichia colicontains at least two. Here we report that B. pertussis waaA encodes an enzyme capable of transferring only a single Kdo during the biosynthesis of LPS and that this activity is sufficient to complement an E. coli waaA mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…We report here the first functional characterization of heptosyltransferase II (WaaF) and extended characterization of heptosyltransferase I of E. coli, glycosyltransferases involved in the biosynthesis of the inner core of LPS. In contrast with Kdo transferases which can be monofunctional (Haemophilus influenzae [29], Bordetella pertussis [30]), bifunctional (E. coli [27], Acinetobacter baumannii, A. haemolyticus [10]) or multifunctional (Chlamydiaceae [8,31]), heptosyltransferases I and II of E. coli are strictly monofunctional and thus follow the dogma of glycobiology:`one enzyme±one glycosidic bond'. Although the genes encoding heptosyltransferases in E. coli and S. enterica have been known for years [12,13,32], a functional characterization was difficult because of the complexity of the in vitro assay.…”
Section: Discussionmentioning
confidence: 99%
“…We report here the first functional characterization of heptosyltransferase II (WaaF) and extended characterization of heptosyltransferase I of E. coli, glycosyltransferases involved in the biosynthesis of the inner core of LPS. In contrast with Kdo transferases which can be monofunctional (Haemophilus influenzae [29], Bordetella pertussis [30]), bifunctional (E. coli [27], Acinetobacter baumannii, A. haemolyticus [10]) or multifunctional (Chlamydiaceae [8,31]), heptosyltransferases I and II of E. coli are strictly monofunctional and thus follow the dogma of glycobiology:`one enzyme±one glycosidic bond'. Although the genes encoding heptosyltransferases in E. coli and S. enterica have been known for years [12,13,32], a functional characterization was difficult because of the complexity of the in vitro assay.…”
Section: Discussionmentioning
confidence: 99%
“…However, they were able to inactivate the chromosomal waaA in the presence of a temperature sensitive plasmid with an intact copy of waaA . The corresponding strain E. coli CJB26 has been transformed with plasmids expressing the waaA genes of C. trachomatis [21] and B. pertussis [13], and it has been possible to select at nonpermissive temperature for the loss of the intact, plasmid‐encoded, host‐specific Kdo transferase gene. As these experiments were performed in the E. coli K‐12 background resulting in recombinant strains with complex LPS structures, we have used a genetically defined, waaCF negative strain of E. coli K‐12, named E. coli WBB01, as a recipient for chlamydial waaA genes.…”
Section: Resultsmentioning
confidence: 99%
“…These Kdo transferases have thus been termed multifunctional [8], although their amino acid sequences and deduced secondary structures exhibit no distinguishable partition into different catalytic domains [9–11]. In addition, the chlamydial WaaAs are structurally similar to those from Haemophilus influenzae [12] and Bordetella pertussis [13], which transfer only one Kdo residue, or to those from Escherichia coli [14] and Acinetobacter spp. [11], which synthesize an α‐Kdo‐(2→4)‐α‐Kdo disaccharide linked to lipid A.…”
mentioning
confidence: 99%
“…The Kdo transferase found in these bacteria displays a monofunctional activity in vitro; 94,96,101 however, complementation studies in E. coli strains lacking a functional waaA were not convincing. 94,102 So far, no structural evidence could be presented that one Kdo residue alone is sufficient to allow complementation to a complete LPS structure; however, it was demonstrated that the monofunctional WaaA from H. influenzae is not able to replace the bifunctional WaaA in an E. coli Re mutant. 97 The smallest structure known to support survival is a lipid A substituted with Kdo-phosphate as found in the H. influenzae mutant I69.…”
Section: Single Steps Of Lps Biosynthesismentioning
confidence: 88%